ChemInform Abstract: Sesquiterpenoids with PPARδ Agonistic Effect from a Korean Marine Sponge Ircinia sp. Issue 5 (February 2015) - Hahn, Dongyup; Chin, Jungwook; Kim, Hiyoung; Yang, Inho; Won, Dong Hwan; Ekins, Merrick; Choi, Hyukjae; Nam, Sang‐Jip; Kang, Heonjoong
Abstract Compounds (I) and (IIc) show PPARδ agonistic activities.